2021
DOI: 10.3389/fenrg.2021.592600
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Utilization and Long-Term Storage in Useful Mineral Products by Carbonation of Alkaline Feedstocks

Abstract: Accelerated carbonation is a carbon utilization option which allows the manufacturing of useful products, employing CO2-concentrated or -diluted emission sources and waste streams such as industrial or other processing solid residues, in a circular economy perspective. If properly implemented, it may reduce the exploitation of virgin raw materials and their associated environmental footprint and permanently store CO2 in the form of Ca and/or Mg carbonates, thus effectively contributing to climate change mitiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The results of the one-way experimental optimization of the reaction solution concentration, calcination temperature, and solid−liquid ratio when using sodium hydroxide solution are shown in Figure 2f, g, h, and the carbon dioxide capture rate under the optimal conditions is 98%. Overall, it is possible to accelerate the mineralization of calcium slag to fix CO 2 through pretreatment and other means that lift calcium dissolution, 31 CO 2 hydrolysis, and reaction limitation by the mineralization process.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the one-way experimental optimization of the reaction solution concentration, calcination temperature, and solid−liquid ratio when using sodium hydroxide solution are shown in Figure 2f, g, h, and the carbon dioxide capture rate under the optimal conditions is 98%. Overall, it is possible to accelerate the mineralization of calcium slag to fix CO 2 through pretreatment and other means that lift calcium dissolution, 31 CO 2 hydrolysis, and reaction limitation by the mineralization process.…”
Section: Resultsmentioning
confidence: 99%
“…An examination of these works revealed that 3 papers (10%) utilized experimental methodology, 6 papers (21%) discussed the reported results and compared them with their findings, and 20 papers (69%) cited 1 or more of Dr. Santos’s papers in the introduction section of their papers to explain a concept (Table S1 in the Supporting Information). More details and discussion about these relevant studies ,, are available in the Supporting Information file alongside other analyses on citation usage, publication sources, country, institutional collaboration analyses, and paper classification according to scientific disciplines and the United Nations Sustainable Development Goals. A scientometric analysis is a powerful tool for researchers to gauge the impact of their work and to connect with the broader scientific community beyond what other networking activities, such as conferences and webinars, allow.…”
Section: Scientometric Analysismentioning
confidence: 99%
“…The process of the aforementioned CO2 sink is called mineral carbonation. Magnesium has been reported as the only element that can be carbonated, aside from calcium [19]. Carbonation of MOC is beneficial for MOC as well as the environment since the material is tougher because it has a denser microstructure [20][21][22][23].…”
Section: Sem Characterizationmentioning
confidence: 99%